2010
DOI: 10.1016/j.physbeh.2010.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fatty acid oxidation activates transforming growth factor-beta in cerebrospinal fluid and decreases spontaneous motor activity

Abstract: We have previously reported that transforming growth factor (TGF)-beta in the cerebrospinal fluid (CSF) is involved in the mechanism underlying the regulation of spontaneous motor activity (SMA) by the central nervous system after exercise. However, it remained unclear what physiological condition triggers the activation of TGF-beta. We hypothesized that the shortage of energy derived from fatty acid (FA) oxidation observed in the early phase of exercise activated TGF-beta in the CSF. To test this hypothesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Since TGF-β3 increased noradrenaline levels in the paraventricular and ventromedial hypothalamic nuclei and chemical lesion of noradrenaline input to these nuclei completely abolished the regulatory effect of TGF-β on fat oxidation it has been suggested that TGF-β in the brain enhances fat oxidation via noradrenergic neurons in the paraventricular and ventromedial hypothalamic nuclei ). An inhibitor of FA oxidation could induce an activation of TGF-β in the CSF suggesting that shortage of energy derived from fatty acids leads to the activation of TGF-β (Fujikawa et al, 2011).…”
Section: Involvement In Inflammatory and Neuroendocrine Functionsmentioning
confidence: 99%
“…Since TGF-β3 increased noradrenaline levels in the paraventricular and ventromedial hypothalamic nuclei and chemical lesion of noradrenaline input to these nuclei completely abolished the regulatory effect of TGF-β on fat oxidation it has been suggested that TGF-β in the brain enhances fat oxidation via noradrenergic neurons in the paraventricular and ventromedial hypothalamic nuclei ). An inhibitor of FA oxidation could induce an activation of TGF-β in the CSF suggesting that shortage of energy derived from fatty acids leads to the activation of TGF-β (Fujikawa et al, 2011).…”
Section: Involvement In Inflammatory and Neuroendocrine Functionsmentioning
confidence: 99%
“…TGF-b is known to mediate tissue inflammation and damage accompanied by tissue fibrosis, and it also plays an essential role in activating CFs. TGF-b causes fibroblast activation, proliferation, and differentiation into myofibroblasts which secreting ECM proteins [11,12]. A typical pathway for TGF-b1 signaling involves phosphorylation of SMAD family member (Smad) 2/3, which subsequently binds to Smad4 and causes nuclear translocation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, noradrenergic projections to the hypothalamus, which plays a pivotal role in the regulation of energy metabolism, were activated by intracisternal administration of TGF-␤ (19), and inhibition of fatty acid oxidation by i.p. administration of mercaptoacetate led to an increase in active TGF-␤ in rat CSF (20). From these data, TGF-␤ in the brain seemed to be closely linked to the energy metabolism state in the body and to play an important role in the regulation of energy metabolism.…”
Section: Discussionmentioning
confidence: 81%